(untitled) (Vietnam Journal of Community Medicine, 2021)
This study aims to analyze and evaluate the realities of medical examination and treatment quality by health insurance at district hospitals in Thai Nguyen province in the 2017 - 2020 period, approach from the managers and medical facilities, then proposing some solutions to improve the quality of medical examination and treatment by health insurance in these hospitals for the period of 2021- 2025, contributing to improving the satisfaction of patients in order to reduce the overload of upper - level hospitals.